2020
DOI: 10.1016/j.fsi.2020.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics reveal conserved impacts of rearing density on immune response of two important aquaculture species

Abstract: Background: Infectious diseases represent an important barrier to sustainable aquaculture development. Rearing density can substantially impact fish productivity, health and welfare in aquaculture, including growth rates, behaviour and, crucially, immune activity. Given the current emphasis on aquaculture diversification, stress-related indicators broadly applicable across species are needed. Results: Utilising an interspecific comparative transcriptomic (RNAseq) approach, we compared gill gene expression resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Ingestion of suitable sources of omega-3 PUFA is essential for proper egg development and offspring survival 67 and Schizochytrium represents a sustainable and rich source of DHA for maturing fish 68 . Moreover, given the importance of the early environmental conditions for subsequent development 69 , 70 , the essential fatty acids provided by Schizochytrium and other similar thraustochytrids can have long-term beneficial effects on fish health and growth, as seen in Siberian sturgeon 71 , Nile tilapia 26 , 27 , 46 , 72 , red sea bream 73 , channel catfish 74 , and jade perch 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of suitable sources of omega-3 PUFA is essential for proper egg development and offspring survival 67 and Schizochytrium represents a sustainable and rich source of DHA for maturing fish 68 . Moreover, given the importance of the early environmental conditions for subsequent development 69 , 70 , the essential fatty acids provided by Schizochytrium and other similar thraustochytrids can have long-term beneficial effects on fish health and growth, as seen in Siberian sturgeon 71 , Nile tilapia 26 , 27 , 46 , 72 , red sea bream 73 , channel catfish 74 , and jade perch 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent impact of these altered light regimes on both fish behaviour and health is now being considered. Recent studies have also found parasitic infection can alter host circadian gene expression, further complicating the relationship between parasites, hosts and the rhythms they both follow (Ellison et al ., 2018 , 2020 ). Considering the positive phototactic response of fish lice, aquaculture lights could attract lice to cages and facilitate infection (Trippel, 2010 , Stewart et al ., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled breeding of tilapias led to excessive recruitment, high densities, stunting and low percentage of marketable-size fish, until research on nutrition, culture systems and the development of hormonal sex-reversal techniques in 1970 allowed for monosex populations to be raised in uniform sizes ( 18 ). Consistently, most of the evidence assessing animal welfare in cichlids refers to O. niloticus, usually regarding welfare indicators of stress ( 19 ) or dietary impacts on improving the antioxidant status and general health in this species ( 20 ). However, evidence on welfare indicators in other cichlids is scarce.…”
Section: Teleost Fish As Biological Models For Welfare Indicatorsmentioning
confidence: 99%